Sistem Informasi Platform Pembelajaran Untuk Komunitas Menggunakan Metode Waterfall - Risky Tri Sandi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
This article focuses on designing a learning platform for the community to increase knowledge and skills, as well as encourage and motivate the community to develop creative solutions and ideas for the problems they face to increase competitiveness. The application design will use the waterfall method because it has a well-defined structure with clear documentation for each stage. The results of this research provide a proposal for a website-based learning platform where the community can carry out online learning such as training, online courses, and consultations. The need for evaluation and documentation is on this platform so that the desire for online learning can be increased in terms of effectiveness, quality, and service to the community.